2020
DOI: 10.1111/febs.15325
|View full text |Cite|
|
Sign up to set email alerts
|

Long non coding RNA SLC26A4‐AS1 exerts antiangiogenic effects in human glioma by upregulating NPTX1 via NFKB1 transcriptional factor

Abstract: Malignant gliomas are a heterogeneous group of brain tumors with a poor prognosis, which is largely due to its aggressive invasiveness and angiogenesis. In recent years, it has been found that multiple long noncoding RNAs (lncRNAs) participate in a wide range of biological functions including angiogenesis through the regulation of gene expression in cancers. In this study, we investigate and report the novel role of lncRNA SLC26A4‐AS1 in gliomas, with a novel mechanism involving transcription factors NFKB1 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 30 publications
1
33
0
1
Order By: Relevance
“…The mechanisms exerted by lncRNAs are complicated [46][47][48]. Different subcellular locations of lncRNAs influence their mechanisms of action.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms exerted by lncRNAs are complicated [46][47][48]. Different subcellular locations of lncRNAs influence their mechanisms of action.…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been found that multiple long non-coding RNAs (lncRNAs) are involved in a wide range of biological functions, including angiogenesis, through the regulation of gene expression in cancer [56]. SLC26A4-AS1 lncRNA has been reported to promote NPTX1 transcriptional activity by recruiting nuclear factor kappa B 1 (NF-κB 1), which has an anti-angiogenic effect on glioma cells; the problem is that SLC26A4-AS1 expression is suppressed in glioma cells.…”
Section: Heterogeneitymentioning
confidence: 99%
“…An inflammatory cytokine that promotes EMT and invasiveness of cancer cells. SLC26A4-AS1 promotes the transcriptional activity of NPTX1 by recruiting NFKB1, thereby producing antiangiogenic effects on glioma cells (32). The platelet subtype of phosphofructokinase (PFKP) is a rate-limiting enzyme involved in glycolysis.…”
Section: A B C Dmentioning
confidence: 99%